Competitiveness Through the Prism of the Culture of Innovation - Georgieva, Ivona (Vilnius University Open Series, 2021)
The main goal of every business organisation in the modern world is to constantly increase its competitiveness in the conditions of constant change imposed by the dynamic business environment. The culture of innovation today is perceived as a key factor in increasing the competitiveness of both an organisation and an entire country as it reflects their ability to think creatively, flexibility, information exchange and perception of innovation. This paper aims to present the relationship between the culture of innovation and competitiveness in the context of Bulgarian organisations. It is indicated that the culture of society itself is important for the culture of innovation. Different value systems can be a prerequisite for the development of various innovation practices, which in turn could lead to good results in the innovation activity of the whole country.